2016
DOI: 10.1038/srep38511
|View full text |Cite
|
Sign up to set email alerts
|

Clonal spread of mcr-1 in PMQR-carrying ST34 Salmonella isolates from animals in China

Abstract: Since initial identification in China, the widespread geographical occurrence of plasmid-mediated colistin resistance gene mcr-1 in Enterobacteriaceae has been of great concern. In this study, a total of 22 Salmonella enterica were resistant to colistin, while only five isolates which belonged to ST34 Salmonella enterica serovar Typhimurium (S. Typhimurium) were mcr-1 positive. Four of them shared nearly identical PFGE type, although they were from different host species and diverse geographical locations. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 45 publications
5
45
0
Order By: Relevance
“…Compared to other bacterial species of Enterobacteriaceae , the prevalence rate of mcr-1 in Salmonella was found to be much lower in each of these surveys, regardless of the site of recovery 16 – 20 . The low prevalence of mcr-1 was also reported in a study from China, England and Wales 3 , 21 . However, another study in China reported the high prevalence of Salmonella from animals 9 .…”
Section: Discussionsupporting
confidence: 69%
“…Compared to other bacterial species of Enterobacteriaceae , the prevalence rate of mcr-1 in Salmonella was found to be much lower in each of these surveys, regardless of the site of recovery 16 – 20 . The low prevalence of mcr-1 was also reported in a study from China, England and Wales 3 , 21 . However, another study in China reported the high prevalence of Salmonella from animals 9 .…”
Section: Discussionsupporting
confidence: 69%
“…Compared with the extensive Plasmid-mediated colistin resistance in animals Plasmid-mediated colistin resistance in animals surveys focused on E. coli, to date, limited information is available for mcr-1-carrying Salmonella in China. The ST34 Salmonella isolate was reportedly involved in the spread of the mcr-1 in Salmonella enterica from food animals in China (Li et al, 2016b;Yi et al, 2017). In Japan, a high proportion of colistin-resistant (45%) pathogenic and mcr-1-positive (13%) E. coli were reported in swine production (Kusumoto et al, 2016).…”
Section: Livestockmentioning
confidence: 99%
“…This indicated that the structure ISApl1-mcr-1-pap2-ISApl1 could be inserted into diverse positions of IncHI2 plasmids. Prior to the current study, IncHI2 plasmids bearing mcr-1 have been identified only in strains of E. coli and Salmonella [4,5]. The current study provides insight into the widespread of mcr-1-bearing IncHI2 plasmids in Enterobacteriaceae, which play a remarkable role in the transmission of mcr-1.…”
Section: Emergence Of the Colistin Resistance Gene Mcr-1 In Citrobactmentioning
confidence: 86%